Developing Measurement of Holistic Islamic Religiosity in Indonesia Islamic Banks’ Consumer: A Mixed Method Study - Christiyanto, Wenda Wahyu; Gaffar, Vanessa; Nurali , Nurali; Kurniawan, Indra; Zuhroh, Siti; Anwar, Resa Nurlaela; Nurianah, Nurianah (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2025)
The purpose of this study is to explore religiosity indicators which are then confirmed to measure the holistic Islamic religiosity variable. This study uses a mixed method, exploratory sequential design. The qualitative method is carried out with a systematic literature review, with 76 articles in the final selection process. The quantitative method is carried out by collecting data from 403 Islamic Bank customers in Indonesia using a numeric scale questionnaire, and analyzed using exploratory factor analysis (SPSS) and confirmatory factor analysis (AMOS) techniques. The findings in this study indicate that holistic Islamic religiosity can be measured by 2 dimensions (faith and piety), consisting of 4 indicators (faith dimensions) and 3 indicators (piety dimensions). This study focuses on Islamic Bank customers in the Jakarta, West Java and East Java areas. Further research is expected to confirm this measurement in other regions and other wider business sectors, so that the level of generalization can be even wider. The measurement of the Holistic Islamic Religiosity variable can be used as a reference by researchers who involve religiosity variables in their research, especially in consumer behavior research with an Islamic theme.